The effects of gestalt techniques on interpersonal orientation and behavior of married couples - Posadas, Flordeliza Corcuera (Animo Repository, 1991)
The study investigates whether Gestalt techniques utilized in a 20-hour couples group counseling program given over two weekends would effect more significant changes in interpersonal orientation and behavioral interaction of married couples compared to a Marriage Enrichment seminar, a Values Formation seminar and a no-treatment condition. Outcomes were measured by the Fundamental Interpersonal Relations Orientation-Behavior (FIRO-B) and the Behavior Checklist, Form A and B. The randomized four-group ANOVA pretest-posttest design was used in this study. The subjects were 24 couples, husband of whom were all probationers who were randomly chosen from the 60 married male probationers who were in active supervision. They were randomly assigned to the Gestalt, Marriage Enrichment, Values Formation and Control groups, six couples to a group. All subjects were pretested on the outcome measures and posttested two weeks later after the completion of the treatment groups' treatment programs.To test the hypotheses, a one-way ANOVA was conducted to determine significant differences in interpersonal orientation and behavior among groups followed by a t-test where significant differences were obtained. A test of difference in proportion of positive and negative changes in the direction of interpersonal behavior was done, first within groups to determine the significance of positive changes in each group, and then between groups where significance was noted. Correlations between the self and spouse-perceived changes in behavioral interaction were obtained with the use of the Pearson r. It was concluded that a) Gestalt techniques, a Marriage Enrichment seminar, and a Values Formation are superior to a no-treatment condition in bringing about significant changes in expressed control and decision-making behavior of married couples enabling them to move towards decision-making and acceptance of responsibility when necessary b) Gestalt techniques are superior to a Marriage Enrichment seminar, a Values Formation seminar and no-treatment condition in bringing about greater flexibility and an increased reciprocity in Control behavior both Gestalt techniques and a Marriage Enrichment seminar are more effective in bringing about reciprocity in Inclusion behavior c) Gestalt techniques do not effect more significant changes in the ability of couples to communicate thoughts, feelings and experiences to the other, to be supportive and to show acceptance to the other, as perceived by the self and the spouse, than a Marriage Enrichment seminar, a Values Formation seminar and a no-treatment condition d) Gestalt techniques bring about changes in communication, support and acceptance behavior in the self that translate into behavior highly perceptible to one's spouse than a Marriage Enrichment seminar, a Values Formation seminar and a no-treatment condition.